2020
DOI: 10.3390/jcm9061669
|View full text |Cite
|
Sign up to set email alerts
|

The Anti-Diabetic Drug Metformin Rescues Aberrant Mitochondrial Activity and Restrains Oxidative Stress in a Female Mouse Model of Rett Syndrome

Abstract: Metformin is the first-line therapy for diabetes, even in children, and a promising attractive candidate for drug repurposing. Mitochondria are emerging as crucial targets of metformin action both in the periphery and in the brain. The present study evaluated whether treatment with metformin may rescue brain mitochondrial alterations and contrast the increased oxidative stress in a validated mouse model of Rett syndrome (RTT), a rare neurologic disorder of monogenic origin characterized by severe behavioral an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 63 publications
3
16
1
Order By: Relevance
“…The treatment with free radical scavengers like Trolox—a derivative from vitamin E—rescued mitochondrial functionality and restored synaptic LTP in the hippocampus and hippocampal astrocytes of this RS mouse model [ 131 , 132 ]. Other compounds such as metformin and quercetin rescued the mitochondrial phenotype in whole brains of Mecp2-308 mutant mice and primary astrocytic cultures, respectively [ 133 , 134 ]. The downregulation of Mecp2 in microglia generates increased oxygen consumption, less ATP production, and overexpression of Snat1—a glutamine transporter encoded by Slc38a1 , a Mecp2 target gene previously identified in a ChIP-seq assay [ 135 ].…”
Section: Asd-related Neurodevelopmental Disordersmentioning
confidence: 99%
See 1 more Smart Citation
“…The treatment with free radical scavengers like Trolox—a derivative from vitamin E—rescued mitochondrial functionality and restored synaptic LTP in the hippocampus and hippocampal astrocytes of this RS mouse model [ 131 , 132 ]. Other compounds such as metformin and quercetin rescued the mitochondrial phenotype in whole brains of Mecp2-308 mutant mice and primary astrocytic cultures, respectively [ 133 , 134 ]. The downregulation of Mecp2 in microglia generates increased oxygen consumption, less ATP production, and overexpression of Snat1—a glutamine transporter encoded by Slc38a1 , a Mecp2 target gene previously identified in a ChIP-seq assay [ 135 ].…”
Section: Asd-related Neurodevelopmental Disordersmentioning
confidence: 99%
“…al 2019 [ 144 ] Increased ROS, intensified oxygen consumption Mecp2 -KO mice Hippocampus, cortex Zuliani et. al 2020 [ 133 ] Reduced ATP production, reduced activities of mitochondrial complexes II and V, decreased protein expression of ETC complexes, increased oxidative stress Mecp2-308 mice Whole brain Dave et. al 2020 [ 134 ] Reduced activities of ETC complexes, reduced Ψ m Mecp2 -KO astrocytes Primary cultured astrocytes Ebrahimi-Fakhari et.…”
Section: Asd-related Neurodevelopmental Disordersmentioning
confidence: 99%
“…Importantly, this was accompanied by restoration of mitochondrial complex activities, suggesting that the rescue of the brain energy reservoir may be fundamental to improve cognitive function in RTT. Indeed, maintaining a steady balance between nutrient supply and energy demand is an essential mechanism for preserving higher brain functions under different conditions [39][40][41].…”
Section: Discussionmentioning
confidence: 99%
“…Another promising area for potential Rett therapies, is the repurposing of existing FDA approved compounds. For example, in 2020, it was found that the diabetes drug, metformin, reduces mitochondrial defects and damage from oxidative stress in Mecp2 308 −/+ truncation female mice (Zuliani et al, 2020). Finally, a recently developed compound for Alzheimer's disease reduced motor defects, learning deficits and breathing abnormalities in Mecp2 −/+ female mice with minimal side effects (Kaufmann et al, 2019).…”
Section: Potential Treatments Under Development For Rett Syndromementioning
confidence: 99%